Parent Training Occupational Therapy Program for Parents of Children with Autism in Korea - Sun-Joung L. An (Occupational Therapy International)
Attitudes and beliefs about parent participation in occupational therapy are shifting toward family-centered practice worldwide. However, adopting a family-centered approach in a society such as Korea, where a Confucian culture of hierarchical roles is reflected in a strong medical model, can prove to be very difficult. A parent training program was developed at the HOPE Center, a pediatric occupational therapy center, to bridge the gap between the traditional medical model and the ideal family-centered model. This study examined the effectiveness of the parent training and gauged parents’ perceptions and experiences of a more family-centered approach to therapy. Four parent-child dyads living with autism participated in five months of parent training at the HOPE center. The results on the Canadian Occupational Performance Measure showed that the parent training improved the occupational performance of both children and parents. Six open-ended questions were used to investigate parents’ perceptions and experiences of parent training. Two broad themes emerged: improved self-efficacy and the cultural reality of living with autism in Korea. This study demonstrates that building parent training into an occupational therapy program may optimize the effectiveness of any therapy and introduce a more family-centered approach to therapy while maintaining cultural integrity.